2009
DOI: 10.1039/b816480k
|View full text |Cite
|
Sign up to set email alerts
|

RNA targeting through binding of small molecules: Studies on t-RNA binding by the cytotoxic protoberberine alkaloidcoralyne

Abstract: Interaction of the protoberberine alkaloid coralyne with t-RNA(phe) was investigated using various biophysical techniques. Results of absorption and fluorescence studies revealed that the alkaloid binds to t-RNA exhibiting positive cooperativity. Isothermal titration calorimetry results suggested that the binding of the alkaloid was predominantly enthalpy driven with a smaller favourable entropy term. A surprisingly large favourable component for non-electrostatic contribution to the binding of coralyne to t-R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 52 publications
2
67
0
Order By: Relevance
“…27 Similar trend was also observed in case of drug-tRNA binding. 28,29 It can be concluded that intermolecular interactions in all the 32 drug-DNA complexes were also supported by intermolecular H-bonds, besides other factors like van der Waal's forces, etc. as revealed by the higher values of energy terms for van der Waal's interactions and electrostatic (table 2).…”
Section: Discussionmentioning
confidence: 97%
“…27 Similar trend was also observed in case of drug-tRNA binding. 28,29 It can be concluded that intermolecular interactions in all the 32 drug-DNA complexes were also supported by intermolecular H-bonds, besides other factors like van der Waal's forces, etc. as revealed by the higher values of energy terms for van der Waal's interactions and electrostatic (table 2).…”
Section: Discussionmentioning
confidence: 97%
“…The free energy contribution from the hydrophobic transfer step of binding of these molecules may be calculated from the relationship [50], ΔG hyd =80(±10) × ΔCp. The ΔG hyd values for thionine binding to CP, HT and ML DNAs were deduced to be −8.1, −10.7 and −16.7 kcal/mol, that are well within the range that was observed for typical intercalating DNA and RNA intercalating molecules [21,24,36,42,44,48,51].…”
Section: Heat Capacity Changesmentioning
confidence: 96%
“…A MicroCal VP-ITC unit (MicroCal, Inc., Northampton, MA, USA) using protocols developed in our laboratory and described in details previously [25,30,35,36] was used for all ITC experiments. A reverse titration protocol of injecting aliquots of DNA solution from a rotating syringe (290 rpm) into the calorimetric cell containing the thionine solution (1.4235 mL) under identical buffer conditions was adopted.…”
Section: Isothermal Titration Calorimetrymentioning
confidence: 99%
“…ITC was performed on a MicroCal VP-ITC microcalorimeter (MicroCal, Inc.). Data acquisition and instrument control were carried out using the dedicated Origin software package using standard protocols reported in [34] [49]. All experiments were conducted at 208.…”
Section: Experimental Partmentioning
confidence: 99%